Sifat Tawâdhu’ Ḥâfidz Al-Qur’an - Sarihat Sarihat (Faculty of Ushuluddin and Humanities, 2018)
Many of Qur'an memorizers include who has become a Hafiz always try to hide the memorization with the reason to keep their heart from feeling proud. Based on the study of the phenomenon, it illustrates the existence of tawâdhu in the Hafiz of the Qur'an themselves. This makes the researcher interested in examining the tawâdhu’ nature fromHafiz of the Qur'an in terms of the Islamic Psychology’s perspective, as well as factors that influence the formation of the tawâdhu’ nature. The research method used is a qualitative method. The subject of the study was six of Hafiz of the Qur'an from students of the Interpretation and Qur’an Science Department at Antasari State Islamic University Banjarmasin. The techniques used are interviews, observation, and documentation. The data were analyzed using a qualitative descriptive method. The result of study show that all subjects fulfill the aspect of tawadhu, like have a self-disclosure nature to others in all positive things without considering wherever it comes, aware of their own shortcomings and introspections, judge themselves as a simple person, pay attention to and respect the differences of each person, and obey to the Allah's commands. There are three levels of tawâdhu seen from the object, they are tawâdhu' to religion, tawâdhu’ to fellow servants of Allah and tawâdhu' to Allah. The five subjects are at the semi tawâdhu’ level, whereas what describes tawâdhu'is only illustrated in one subject. These levels of difference are caused by factors that influence the formation of thetawâdhu’ nature in each subject they are the factors of education, environment, knowledge and life experience.